Penjadwalan Perawatan Komponen Kritis Mesin Tube Mill Pembuat Pipa Baja (Studi Kasus : CV. Perjuangan Steel Surabaya) - Samudera, Satria Putra; Abdulrahim, Muslimin (Innovative: Journal Of Social Science Research, 2024)
Production machinery is an important factor in a manufacturing enterprise, if the production machine is often damaged then it will affect the production process. Engine damage caused downtime so the machine could not produce. On the CV. Surabaya Steel Struggle there is a Tube Mill machine that produces Steel Pipe. This machine is often damaged causing downtime. This machine has several submachines in it, the submachine that has the highest downtime is the Welding table machine. With this application this study aims to find out the critical components of the damage of the welding table and to know the intervals of change of critical parts. Using ABC analysis can determine the critics of the components on the welded table machine and then look for the treatment intervals for critical elements with age replacement method. So you can make a care schedule based on downtime. Based on the data processing that has been done, the result is that the components that fall into the critical engine category are RF Card Module, Oscillator Board and Power Supply Board with alternating intervals of 500 hours (21 days), 450 hours (19 days) and 450 hours respectively. (19 Hari).